The impact of predation on population dynamics of the Crested Ibis in the Qinling Mountains, Shaanxi, central China. Issue 3 (30th June 2022) - Jiang, Nan; Wu, Si; Tong, Yi‐Wei; Zhang, Ya‐Zu; Li, Xia; Ye, Xin‐Ping; Yu, Xiao‐Ping
Abstract : Predation is one of the most important extrinsic factors acting upon animal populations and is a strong selective force in the evolution of form and function. Understanding the impact of predation on bird population dynamics is crucial for understanding the predation pressure of bird populations and implementing conservation strategies, especially for threatened or endemic bird species. In this paper, we sorted the predation events in the wild Crested Ibis population in Yangxian County, Shaanxi Province, from 1981 to 2021 and in the reintroduced Crested Ibis population in Ningshan from 2008 to 2021. With the use of age‐classified Leslie matrix models to simulate Crested Ibis populations under different predation pressures, the random population growth rate was estimated, and the impact of predation on population dynamics was evaluated. The results showed that snakes and raptors were the main predators of Crested Ibis in the wild and reintroduced populations, and the number of dead individuals was unevenly distributed within the three age classes in both the wild population ( df = 2, χ 2 = 13.236, p < 0.05) and reintroduced population ( df = 2, χ 2 = 49.273, p < 0.01). Predation caused a reduction in the potential annual population growth rate of 2.37% (confidence interval [CI]: 2.29–2.45) in the wild population and 2.88% (CI: 2.82–2.94) in the reintroduced population. The overall average growth rates of the wild and reintroduced populations derived from population model simulations were 12.84 and 18.13%, respectively, which suggested that the wild and reintroduced populations was increasing under the current predation pressure and that the impact of predation on the population was acceptable and sustainable.